Report of isolation of Cryptobacterium curtum from a pelvic abscess. Issue 4 (August 2015) - Sridhar, Siddharth; Wong, Samson S.Y.; Tam, Emily W.T.; Lau, Susanna K.P.; Woo, Patrick C.Y.
Abstract : Introduction: To the best of our knowledge, this is the first reported case of isolation of Cryptobacterium curtum from an infected site outside the oral cavity. Case presentation: We report a patient who presented with fever and abdominal pain following an endoscopic procedure. Imaging confirmed a retroperitoneal abscess secondary to duodenal perforation complicating the endoscopic procedure. Surgical drainage of the abscess was carried out. Microbiological analysis of the pus revealed, among other bacteria, an anaerobic Gram-positive rod-shaped bacterium that was definitively identified as Cryptobacterium curtum by 16S rRNA gene sequencing. The patient improved after multiple episodes of retroperitoneal lavage and a prolonged course of antibiotics. Conclusion: This case demonstrates that C. curtum can be isolated outside the oral cavity in polymicrobial infected sites. The pathogenic significance of this organism in contributing to pyogenic infection requires further study.